The Impact of Video Conferencing Platform in All Educational Sectors Amidst Covid-19 Pandemic - Froilan D Mobo (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The Impact of COVID-19 Pandemic made the business world stop and also the economic sector. Health protocols standard has been observed like social distancing, the mandatory wearing of facemask, and avoiding mass gathering. The researcher is proposing to use a video conferencing platform beside the learning management system because this will replace the face to face setup and realtime feedback from the students to the teacher. Video conferencing has always been a key ingredient in the recipe to success for enterprises and other educational sector hoping to connect with customers, remote workers, and even with the students, (BEAUFORD, 2020). The results suggest that current policies and teaching strategies can be adapted due to the outbreak of COVID-19. In relation to previous studies on the use of videoconferencing in higher education, Video Conferencing such as Zoom and Google meet the demands in a broader consideration of the relevant challenges that arise when using certain videoconferencing systems in learning and teaching situations and that can be used in the current scenario, (Khatib, 2020). Using Video Conferencing will not violate any quarantine protocols and this will ensure the safety of both students and the teachers, in times like this, we really need to adopt the new technology platforms embracing the effects of COVID-19 and might lead to the opening of the New Normal in all sectors.